Learning History Courseware for form 4 student (i-Sejarah) / Nur Farhana Mohd Pauzi - Mohd Pauzi, Nur Farhana (2015)
The development of computer technology nowadays makes life easier in various aspects. Technology is also widely applied in undergoing the process of teaching and learning. Courseware is one of the learning processes where the elements of multimedia like image, audio, text, animation and video are being integrated to produce an effective courseware. Because of the interesting use of technology, History courseware will be developed as History is one of the important subjects as it acts like a tool or guideline in creating a civilization citizen. This courseware entitled i-Sejarah. To develop the courseware, a preliminary study has been carried out to identify the suitable method to use. Based on the previous study, ADDIE Model has been chosen to be a guideline in developing this courseware. There are five process in ADDIE Model which are analyze, design, develop, implement and evaluate. When the development is done, the courseware is being evaluated by users and expert users. The purpose of courseware evaluation is to know whether the courseware fulfill the requirements of the users or not. The courseware was tested by the developer of the courseware and a tester at the first place. Then the courseware was evaluated by the experts and users. There are 30 respondents and three experts that evaluate the i-Sejarah courseware.